From Discovery to the First Month of the Type II Supernova 2023ixf: High and Variable Mass Loss in the Final Year before Explosion - Hiramatsu, Daichi; Tsuna, Daichi; Berger, Edo; Itagaki, Koichi; Goldberg, Jared A.; Gomez, Sebastian; Kishalay De; Hosseinzadeh, Griffin; Bostroem, K. Azalee; Brown, Peter J.; Arcavi, Iair; Bieryla, Allyson; et al. (Astrophysical journal. Letters, 2023)
We present the discovery of the Type II supernova SN 2023ixf in M101 and follow-up photometric and spectroscopic observations, respectively, in the first month and week of its evolution. Our discovery was made within a day of estimated first light, and the following light curve is characterized by a rapid rise (≈5 days) to a luminous peak ( M V ≈ − 18.2 mag) and plateau ( M V ≈ − 17.6 mag) extending to 30 days with a fast decline rate of ≈0.03 mag day −1 . During the rising phase, U − V color shows blueward evolution, followed by redward evolution in the plateau phase. Prominent flash features of hydrogen, helium, carbon, and nitrogen dominate the spectra up to ≈5 days after first light, with a transition to a higher ionization state in the first ≈2 days. Both the U − V color and flash ionization states suggest a rise in the temperature, indicative of a delayed shock breakout inside dense circumstellar material (CSM). From the timescales of CSM interaction, we estimate its compact radial extent of ∼(3–7) × 10 14 cm. We then construct numerical light-curve models based on both continuous and eruptive mass-loss scenarios shortly before explosion. For the continuous mass-loss scenario, we infer a range of mass-loss history with 0.1–1.0 M ⊙ yr −1 in the final 2−1 yr before explosion, with a potentially decreasing mass loss of 0.01–0.1 M ⊙ yr −1 in ∼0.7–0.4 yr toward the explosion. For the eruptive mass-loss scenario, we favor eruptions releasing 0.3–1 M ⊙ of the envelope at about a year before explosion, which result in CSM with mass and extent similar to the continuous scenario. We discuss the implications of the available multiwavelength constraints obtained thus far on the progenitor candidate and SN 2023ixf to our variable CSM models.